Optimising Foliar Feeding Rate of Seaweed Based Biostimulant (Crop Plus) For Transplant Aman Rice Varieties (Journal of the Bangladesh Agricultural University, 2026)
Seaweed extract-based biostimulants are gaining increasing attention in modern agriculture for their ability to stimulate physiological processes, growth and productivity of crops without any environmental pollution. In many cases, indiscriminate application of seaweed extract leads to inconsistent results and reduced economic return. But seaweed extract is yet to be explored for increased rice productivity under Bangladesh conditions. To recognize the most suitable application rate of seaweed extract for transplant Aman rice, a field experiment was conducted at the Bangladesh Agricultural University following a randomized complete block design with three replications comprising two rice varieties namely, BRRI dhan75 and BRRI dhan87 and five application rates of seaweed based biostimulant ‘Crop Plus’ such as no Crop Plus (control), 300 mL ha-1, 400 mL ha-1, 500 mL ha-1 and 600 mL ha-1.  Foliar application of Crop Plus at different growth rates significantly enhanced the growth and yield performance of T. Aman rice. The variety BRRI dhan87 consistently outperformed BRRI dhan75 in most growth, yield attributes and yield, but BRRI dhan75 was more responsive to Crop Plus. Although applying Crop Plus @ >400 mL ha⁻¹ did not result in additional yield advantages, economic returns increased progressively up to the highest application rate of 600 mL ha⁻¹. Based on the economic analysis, the application of Crop Plus at 600 mL ha⁻¹ in two splits at 40 and 60 days after transplanting is recommended for T. Aman rice. Although BRRI dhan75 showed greater responsiveness to Crop Plus, BRRI dhan87 may be preferred for cultivation due to its higher productivity.J Bangladesh Agril Univ 24(2): 81–91, 2026